La esclerosis en placas en el Perú: ¿es más común de lo que se pensaba clásicamente? - Trelles, L.; Castro, C.; Díaz, A.; Velasco, R.; Montano, S.; Meza, M.; Trelles, M.P. (Revista de Neuro-Psiquiatría, 2013)
.